The Effect of Vasten Puki Yoga on Reduction of Incontinence in the Elderly - Dwi Sulistyowati; Rita Benya Adriani (Indonesian Journal of Global Health Research, 2025)
Urinary incontinence is defined by the international continence society as a condition where uncontrollable urine output is a social or hygienic problem in the elderly and can be objectively proven. This study is looking for a model of gymnastic movements that are suitable for overcoming incontinence in the elderly, in the first year looking for gymnastic movements and getting a Vasten Puki Yoga gymnastics model that can be used as one of the effective interventions to control incontinence, which has been tested on elderly people in 5 elderly homes and get significant results without finding difficulties, which means that the Vasten Puki Yoga gymnastics movement can be used in the elderly. and in the second year the Vasten Puki Yoga gymnastics movement was used for research at Dr. Moewardi Surakarta Hospital. This study used a pre-experimental research design, namely one group pretest-postest. The population of this study were elderly people who experienced incontinence in nursing homes and poly Geriatric Hospital Dr. Moewardi Surakarta A total of 80 respondents with total sampling technique. The results of the Paired Sample T-test showed an average difference between pre-test and post-test of 8.30 with a significance value (2-tailed) of 0.000 <0.05. Yoga Vasten Puki exercise is an exercise designed with light movements for the elderly to reduce the frequency of micturition, because it can enable or activate the pelvic muscles. Yoga Vasten Puki exercise can be effective if done regularly at least twice a day and the movement is repeated 3 times for 4 weeks to reduce the frequency of micturition.